2012
DOI: 10.1021/jp307454y
|View full text |Cite
|
Sign up to set email alerts
|

Energy Alignment, Molecular Packing, and Electronic Pathways: Zinc(II) Tetraphenylporphyrin Derivatives Adsorbed on TiO2(110) and ZnO(11–20) Surfaces

Abstract: The relation between energy alignment, adsorption geometry, and electron transfer between a chromophore and an oxide surface has been explored for a series of Zn(II) tetraphenylporphyrin derivatives adsorbed on TiO2(110) and ZnO(112̅0) surfaces. The electronic occupied and unoccupied structure has been obtained using UV-photoemission and inverse photoemission spectroscopies. From these results, a full picture of the energetics at the chromophore–oxide interface was established. The alignment of the molecular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 66 publications
(144 reference statements)
3
74
0
Order By: Relevance
“…Although not rigorously appropriate for TPP and TAPP, the molecular symmetry of the MO and excited states refers, for simplicity, to D 2h free-base porphine. Measuring both the filled and empty states of a system gives access to its electronic transport energy gap (E g ) [48][49][50]. This is given by the energy separation between the leading edges at the HOMO and LUMO intersecting the zero-emission baseline (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although not rigorously appropriate for TPP and TAPP, the molecular symmetry of the MO and excited states refers, for simplicity, to D 2h free-base porphine. Measuring both the filled and empty states of a system gives access to its electronic transport energy gap (E g ) [48][49][50]. This is given by the energy separation between the leading edges at the HOMO and LUMO intersecting the zero-emission baseline (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of techniques were used such as scanning tunneling microscopy (STM) to gain insight into adsorption geometries, near edge X-ray absorption fine structure (NEXAFS) to elucidate intramolecular features such as the relative orientation of the phenyl groups with respect to the macrocycle, 25,26,32,[40][41][42][43][44][45] Xray, 17,21,33,34,[37][38][39][41][42][43][44][45][46][47] ultraviolet, 17,28,34,40,46,47 and inverse 17,28,40 photoemission spectroscopy (XPS, UPS, and IPS) to probe directly the electronic structure and chemistry, and temperature programmed desorption (TPD) to track molecular desorption and hydrogen evolution with temperature. 27,33,48 On metal surfaces, due a strong porphyrin core iminic nitrogenssubstrate interaction, the mesophenyls are typically rotated and can even become coplanar with the porphyrin core.…”
Section: Introductionmentioning
confidence: 99%
“…15 Song et al 4 showed that diarylamine chlorosilane (Ar 2 N-(CH 2 ) n -SiCl 3 , Ar = 3,4-difluorophenyl) redox-active modifiers can serve as a hole-selective interfacial layer on an ITO electrode in bulk-heterojunction OPVs; the PCE of these devices was slightly higher than that of devices in which PEDOT:PSS was utilized as the interfacial layer. 4 These and other papers [15][16][17][18][19][20][21] have demonstrated that the molecular design of a redox-active modifier, such as the type, position and length of its bridging moiety and the presence of solubilizing groups or bulky substituents, may significantly affect the charge-collection kinetics and efficiency at modified TCO surfaces, because these structural parameters dictate properties such as molecular orientation, tunneling distance, degree of aggregation, and/or interface dipole magnitude and orientation.…”
Section: Introductionmentioning
confidence: 99%